Penerapan Etika Bisnis Islam Terhadap Bisnis Multi Level Marketing (MLM) Stokis Herba Penawar Al Wahida Indonesia (HPAI) Di Keppo Polagan Galis Pamekasan - Rahmah, Widadatur; Hakim, Lukmanul (Mabny: Journal of Sharia Management and Business, 2022)
Abstract: Multi-Level Marketing (MLM) business is a business whose marketing strategy is tiered or tiered. The purpose of the tiered marketing is a marketing in which the sales force (stockist) not only gets a profit based on product sales, but also gets it based on the sales of other stockists who are recruited to become members. This MLM business is in great demand by the public, but recently a problem has arisen regarding the presence of the MLM business. People are victims of money games, unfair marketing strategies, giving product testimonials that are not real and there is an element of fraud that creates unrest in the community. One of the reasons for this is that business actors do not apply Islamic business ethics to their business operations. So many parties feel disadvantaged. Herba Penawar Al Wahida Indonesia (HPAI) is one of the sharia-based MLM businesses in Indonesia. HPAI sharia MLM is here as if to give an answer to the public that not all MLM businesses are detrimental. This study aims to determine marketing strategies and provide testimonials for HPAI MLM business products which are analyzed based on Islamic business ethics. The results of the study stated that the marketing strategy and giving HPAI product testimonials to consumers in general had implemented the five principles of Islamic business ethics. Among them are the principle of oneness, the principle of justice, the principle of free will, the principle of truth and the principle of responsibility. Keywords: Islamic Business Ethic, Multi Level Marketing